Parental imprisonment, childhood behavioral problems, and adolescent and young adult cardiometabolic risk: results from a prospective Australian birth cohort study - Michael E. Roettger; Jolene Tan; Brian Houle; Jake M. Najman; Tara McGee (Health & Justice)
Abstract Objectives Recent studies have demonstrated that parental imprisonment (PI) is associated with cardiometabolic risk later in life. However, underlying risk factors for these associations have not previously been explored. Using a life course framework, the present study explores how early childhood emotional and behavioral dysregulation and PI may be associated with progressive cardiometabolic risk factors in adolescence and young adulthood among male and female respondents in an Australian birth cohort. Methods The study follows a subset of 7,223 live, singleton births from 1981 to 1984 in Brisbane, Australia where data was collected on parental imprisonment at ages 5 & 14 and behaviors from the Child Behavioral Checklist (CBCL) at age 5. Our sample examines 1,884 males and 1,758 females whose mothers completed prenatal, age 5, and age 14 interviews and respondents completed one or more interviews at a health clinic at ages 14, 21, and 30. Multivariate regression was used to examine cross-sectional results, while individual growth models examined longitudinal patterns. Results Dividing the analysis by sex, we examined how parental imprisonment was potentially mediated or moderated by CBCL subscale measures for aggression, social-attention-thought (SAT) disorders, internalizing, and depression. No associations were found among male respondents. Among female respondents, controlling for these behaviors, there was a significant association between parental imprisonment and higher systolic blood pressure at age 30, while all CBCL measures were found to moderate waist circumference at age 30 and BMI at ages 14, 21, and/or 30. Using individual growth curve modelling, we observed the increased CBCL aggression and SAT scores were increasingly associated with higher BMI as respondents aged in adulthood. Conclusions Using prospective cohort data, our results suggest that PI and emotional and behavioral dysregulation are associated with BMI, systolic blood pressure, and waist circumference in females, along with potentially increasing levels of cardiometabolic risk, as measured by increased BMI, from age 14 through age 30. The result is suggestive of the importance of examining early emotional/behavioral problems and PI as joint risk factors for developing cardiometabolic risk factors that may progress into cardiometabolic diseases at later stages in the life course.